Bioinformatic discovery of novel bioactive peptides - Edwards, Richard J; Moran, Niamh; Devocelle, Marc; Kiernan, Aoife; Meade, Gerardene; Signac, William; Foy, Martina; Park, Stephen D E; Dunne, Eimear; Kenny, Dermot; Shields, Denis C (Nature chemical biology, 2007)
Short synthetic oligopeptides based on regions of human proteins that encompass functional motifs are versatile reagents for understanding protein signaling and interactions. They can either mimic or inhibit the parent protein's activity 1 , 2 , 3 , 4 and have been used in drug development 5 . Peptide studies typically either derive peptides from a single identified protein or (at the other extreme) screen random combinatorial peptides 4 , 6 , often without knowledge of the signaling pathways targeted. Our objective was to determine whether rational bioinformatic design of oligopeptides specifically targeted to potentially signaling-rich juxtamembrane regions could identify modulators of human platelet function. High-throughput in vitro platelet function assays of palmitylated cell-permeable oligopeptides corresponding to these regions identified many agonists and antagonists of platelet function. Many bioactive peptides were from adhesion molecules, including a specific CD226-derived inhibitor of inside-out platelet signaling. Systematic screens of this nature are highly efficient tools for discovering short signaling motifs in molecular signaling pathways.